ANALISIS FAKTOR YANG MEMPENGARUHI ALIH FUNGSI LAHAN PADI KE KELAPA SAWIT DI KECAMATAN SERUYAN HILIR TIMUR: Rita Setiawati1), Parissa Swasti RN2), Tirsa Neyatri Bandrang3) - Rita Setiawati; Tirsa Neyatri Bandrang; Parissa Swasti RN (Politeknik Seruyan, 2025)
This study aims to analyze the factors influencing the conversion of paddy fields into oil palm plantations in Seruyan Hilir Timur District, Seruyan Regency, Central Kalimantan. This land-use change has become a major concern due to the significant decrease in paddy field area, while the area of oil palm plantations continues to increase. The study employs a quantitative method with a survey approach targeting farmers who have converted their land. Data were collected through questionnaires and analyzed using multiple linear regression to identify the influencing factors. The results indicate that economic factors, such as the selling price of harvests and higher income from oil palm, are the main drivers for farmers to convert their land. Additionally, environmental and technical factors also play a role in the farmers' decision-making, although their influence is not as strong as that of economic factors. The conclusion of this study is that economic factors are the most significant determinants in the conversion of paddy fields to oil palm plantations in Seruyan Hilir Timur District. Keywords: Land use change, Economic factors, Environmental factors, Technical factors